Parents’ and Teachers’ Perception of Indicators for The Choice of Marriage Partner Among Hearing-Impaired Adults - Adedayo Adesokan; Adeleye O. Oyunniyi; Salamat I. Abdulgafar (Universitas Pendidikan Indonesia (UPI), 2024)
The study examined the parents’ and teachers’ perceptions of the indicators for the choice of marriage partners among hearing-impaired adults. A descriptive survey research design was used and the sample size was 400 respondents which were purposively selected. The instrument for data collection was a questionnaire titled Indicators for Choice of Marriage Partners Questionnaire. Three research questions and hypotheses were generated for the study. The findings of the study revealed that parents' and teachers’ perception of the indicators for the choice of marriage partners among hearing-impaired adults in Kwara Nigeria is positive. There was a significant difference between the parents’ and teachers’ perceptions, but no significant difference between the parents’ perceptions based on gender. There was a significant difference between the teachers’ perceptions based on gender. It was concluded that parents and teachers have a positive perception of the indicators for choice of marriage partners among hearing-impaired adults therefore it was recommended that Parents and teachers should help their hearing-impaired adults to consider some indicators when they want to choose a marriage partner.